The simulation of the direct torque control of permanent magnet synchronous motor - Dalib, Sariati (2007)
The direct torque control theory has achieved great success in the control of induction motor. Many attempts have been made to implement the idea of DTC of induction motor to PMSM since 1990’s. The DTC is implemented by selecting the proper voltage vector according to the switching status of inverter which was determined by the error signals of reference flux linkage and torque with their measured real value acquired by calculating in the stationary reference frame by means of simply detecting the motor voltage or currents. Aiming at the DTC in PMSM Drives, this project explained the theoretical basis of the direct torque control (DTC) for PMSM firstly. Then explained the difference between the application of DTC to PMSM and to IM. Finally the Matlab/Simulink models were developed to examine the DTC for PMSM and IM. The simulation results is presented and explained in detail.